2020
DOI: 10.1530/erc-19-0341
|View full text |Cite
|
Sign up to set email alerts
|

Mebendazole inhibits tumor growth and prevents lung metastasis in models of advanced thyroid cancer

Abstract: The most common thyroid malignancy is papillary thyroid cancer. While a majority respond to therapy and have a favorable prognosis, some papillary thyroid cancers persist. This subset may dedifferentiate to anaplastic thyroid cancer, an aggressive, highly invasive and rapidly fatal cancer. Thyroid cancer patients at risk for disease progression and metastasis need earlier, safer and more effective therapies. The purpose of this translational study was to determine if mebendazole could be repurposed to effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 60 publications
(68 reference statements)
2
27
0
Order By: Relevance
“…We demonstrated that MBZ exerted more potent anti-proliferation activity than cisplatin in human HNSCC cells, and effectively inhibited cell proliferation, cell cycle progression and cell migration, and induced apoptosis in HNSCC cells [ 18 ]. Other studies indicate that MBZ and its derivatives exerted potent anticancer effect in non-small cell lung cancer [ 19 , 20 ], adrenocortical carcinoma [ 22 ], medulloblastoma [ 28 ], melanoma [ 21 ], leukemia and myeloma [ 24 ], glioblastoma multiform [ 23 , 34 ], colon cancer [ 26 ], cholangiocarcinoma [ 27 ], breast cancer [ 25 , 29 ], gastric cancer [ 30 ], mouse hepatoma [ 31 ], and thyroid cancer [ 32 ]. In this study, our results are the first to demonstrate that MBZ can overcome cisplatin resistance and synergize with cisplatin in inhibiting cell proliferation and inducing apoptosis in cisplatin-resistant ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that MBZ exerted more potent anti-proliferation activity than cisplatin in human HNSCC cells, and effectively inhibited cell proliferation, cell cycle progression and cell migration, and induced apoptosis in HNSCC cells [ 18 ]. Other studies indicate that MBZ and its derivatives exerted potent anticancer effect in non-small cell lung cancer [ 19 , 20 ], adrenocortical carcinoma [ 22 ], medulloblastoma [ 28 ], melanoma [ 21 ], leukemia and myeloma [ 24 ], glioblastoma multiform [ 23 , 34 ], colon cancer [ 26 ], cholangiocarcinoma [ 27 ], breast cancer [ 25 , 29 ], gastric cancer [ 30 ], mouse hepatoma [ 31 ], and thyroid cancer [ 32 ]. In this study, our results are the first to demonstrate that MBZ can overcome cisplatin resistance and synergize with cisplatin in inhibiting cell proliferation and inducing apoptosis in cisplatin-resistant ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…[385][386][387] In further agreement, a recent study reported that mebendazole reduced GLI1 expression in advanced thyroid cancer. 388 Mebendazole was also shown to have anticancer activity and enhanced cisplatin-induced DNA damage, by inhibition of DNA doublestrand break repair, in head and neck squamous cell carcinoma. 389 Interestingly, benzimidazole derivatives were reported as potential dual inhibitors for PARP-1 and DHODH, two key proteins involved in DNA replication and repair mechanisms, respectively.…”
Section: Non-oncology Drugs In Drug Repurposingmentioning
confidence: 99%
“…Supplementary Table 1 ( 4 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 ) summarizes the antitumorigenicity of benzimidazole anthelmintics on cancer cell lines. Benzimidazole anthelmintics inhibit the progression of cancer through a variety of mechanisms.…”
Section: Antitumorigenic Effects Of Benzimidazole Anthelmintics In Camentioning
confidence: 99%
“…We summarized the antitumorigenicity of benzimidazole anthelmintics in animal tumor models ( Supplementary Table 2 ) ( 4 8 11 12 13 14 15 16 17 20 27 28 29 30 34 35 36 37 39 45 47 51 52 54 55 56 57 61 63 64 65 66 69 70 71 74 75 76 78 79 80 92 93 94 ). Benzimidazole anthelmintics have been shown to inhibit the tumor growth in animals, which have been well-tolerated without significant side effects during the experimental period.…”
Section: Antitumorigenic Effects Of Benzimidazole Anthelmintics In Anmentioning
confidence: 99%